Migration when social preferences are ordinal: Steady-state population distribution, and social welfare - Oded Stark (University of Tübingen, Faculty of Economics and Social Sciences, 2017)
This paper adds three dimensions to the received literature: it models migration when the individuals' preferences regarding their relative income are ordinal, it works out the resulting spatial steady-state distribution of the individuals, and it shows that the aggregate of the individuals' migration choices in the spatial steady-state distribution sums up to the social optimum. This finding does not apply when the individuals' preferences regarding their relative income are cardinal. We highlight the importance of the assumption about the nature of the individuals' social preferences (whether ordinal or cardinal) to studying and predicting their migration behavior, and to elucidating the consequences of that behavior for social welfare.
urn:nbn:de:bsz:21-dspace-761989
Keywords: C61; C62; D50; D60; D62; I31; R13; R23; Z13; 330; Ordinal preferences; Distaste for low relative income; An ordinal measure of income relative deprivation; Interregional migration; Steady-state spatial distribution; Social Welfare